The Influence of Flight Delays on Nam Air Airlines on Interest in Purchasing Tickets at Iskandar Pangkalan Bun Airport, Central Kalimantan - Yan Syahni; Septiyani Putri Astutik (AURELIA: Jurnal Penelitian dan Pengabdian Masyarakat Indonesia, 2023)
Because the Unitary State of the Republic of Indonesia is a very large archipelagic country with many islands, inter-island travel requires a mode of transportation. The rapid population growth demands the development of transportation as a means to assist people in meeting their needs. This encourages the public and private sectors to build effective transportation facilities. As a result of these developments, airlines often make mistakes such as flight delays. NAM AIR is one of the private airlines that often delays flights at Iskandar Pangkalan Bun Airport, Central Kalimantan. The purpose of this study was to determine the effect of flight delays on the intention to buy tickets for NAM AIR airlines and how much influence they have on purchasing intentions for NAM AIR airlines. Data collection was carried out by distributing questionnaires in this quantitative study using a purposive sampling technique and a sample of 100 respondents. Using SPSS 21, Descriptive Test, Simple Classical Assumption Test, and Hypothesis Test (T-T) were used for data analysis. Based on the calculated T value of 4.557 and T table of 1.660, the H1 hypothesis is accepted. This shows that the independent variable (flight delay) has an effect on the dependent variable (ticket purchase intention) on the NAM AIR airline at Iskandar Pangkalan Bun Airport, Central Kalimantan. The R Square value of 0.176 indicates that the flight delay variable has an effect of 17.6% on the interest in buying NAM AIR airline tickets at Iskandar Pangkalan Bun, Central Kalimantan.